China's and India's roles in global trade and finance - twin titans for the new millennium? - Matthieu Bussière; Arnaud Mehl (European Central Bank (ECB), 2008)
This paper analyses the integration of China and India into the global economy. To this end, it presents estimates from a gravity model to gauge the overall degree of their trade intensity and the depth of their bilateral trade linkages, as well as selected measures of revealed comparative advantage and economic distance. The paper also reviews the key characteristics of the two countries' domestic economies that are relevant to their global integration and analyses their financial linkages with the rest of the world. Four main fi ndings stand out. First, considering trade in goods, the overall degree of China's trade intensity is higher than fundamentals would suggest, whereas the converse is true for India. Second, Chinese goods exports seem to compete increasingly with those of mature economies, while Indian exports remain more low-tech. Third, China's exports of services tend to complement its exports of goods, while India's exports are growing only in deregulated sectors, such as IT-related services. Last, China's and India's roles in the global financial system are still relatively limited and often complementary to their roles in global trade.
Keywords: E44; F3; C5; 330; China; India; global trade; gravity models; competitiveness indicators; global finance.; Internationale Wirtschaftsbeziehungen; Globalisierung; Internationaler Wettbewerb; Internationaler Finanzmarkt; China; Indien